Esensi Pendidikan Berkarakter di Tengah Maraknya Fenomena Sarjana Pengangguran - Amilah Munadziroh; Dzulfani Nur Hidayanti; Hikmah Irmadika Putri; Rinjania Rinjania; Riza Natania Zulyatina; Dadi Mulyadi Nugraha (Jurnal Ecogen, 2023)
Entering the world of work in Indonesia is not an easy thing, because Indonesia is still facing a gap between undergraduate graduates and employment which causes the unemployment rate to increase. Apart from that, character education is important to improve a person's skills at work. This lack of knowledge about character education is what caused the writing team to investigate this case, and hope that the generation of researchers can understand the importance of character education. The literature study research method is the research method chosen to explore the problem of unemployment among undergraduate graduates. The importance of character education in higher education is an effort to integrate the character development of undergraduate graduates who are not only professional but also have integrity and have good ethical values. Apart from being able to reduce unemployed graduate graduates, character education will also create a young generation who have a good identity and good manners for the future. Character education is not just something that is needed for life in the world, but in religion, character education is also very necessary. By discussing the importance of character education, it is hoped that Indonesia's young generation will better understand the essence of character education itself.